Relationship of Spiritual Intelligence with achievement among 11th grade students in Al Suwaiq in the Sultanate of Oman - al-Kiyumi, Muhammad bin Talib bin Muslim; Al-Farisiah, Saja bint Saeed bin Khamis (Journal of Educational and Psychological Sciences, 2018)
This study examined the size and direction of the relationship between spiritual intelligence and academic achievement. Correlation methodology was employed to investigate the association between study’s variables: spiritual intelligence and academic achievement, in addition of examining the statistical significant differences on the spiritual intelligence with regard to gender. The sample consists 249 students of 11th grade in Al- Suwaiq city. Spiritual intelligence inventory (King, 2008) was employed after measuring content validity which constitute item validity and sampling validity. Internal consistency reliability was measured by Cronbach Alpha, and the coefficient was high r= 0.80. In addition of these psychometric properties, the researchers examined exploratory factor analysis. The findings showed that the spiritual intelligence was high M= 3.64, in addition of academic achievement of Islamic Education M= 77.23. The findings also showed that there was a weak and negative relationship between spiritual intelligence and academic achievement, r= -0.06. Moreover, there was a statistical differences in the spiritual intelligence with regard to gender in favor of female. Based on these findings, the researchers recommended that individual differences should be considered by the teachers through teaching process. Islamic Education curricula should emphasis on developing spiritual intelligence among the students. Additionally, the instructions and students exercises should be varied in teaching spiritual intelligence for male and female. The teacher’s guidance of Islamic culture curricula must include instructions about teaching multiple intelligences, especially spiritual intelligence.
Keywords: spiritual intelligence; academic achievement; Suwaiq; Sultanate of Oman